2023
DOI: 10.2196/41740
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Cancer Journey Using Web-Based Information: Grounded Theory Emerging From the Lived Experience of Cancer Patients and Informal Caregivers With Implications for Web-Based Content Design

Abstract: Background The internet is an important source of information for many informal caregivers and patients living with cancer. A better understanding of how individuals use the internet to meet their informational needs is important for guiding intervention development. Objective The objectives of this study were to develop a theory describing why individuals living with cancer use the internet to find information, characterize the challenges faced with ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
6
0
2
Order By: Relevance
“…First, very few questionnaires were identified that are suitable for assessing information needs regarding specific cancer challenges (Thiessen et al 2023). Of the 21 questionnaires, only 7 focused on specific challenges arising during the cancer journey such as curative intent treatment decision-making in prostate cancer (D' Alimonte et al 2011;Feldman-stewart et al 2001) or lymphedema in the breast cancer context (Dorri et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, very few questionnaires were identified that are suitable for assessing information needs regarding specific cancer challenges (Thiessen et al 2023). Of the 21 questionnaires, only 7 focused on specific challenges arising during the cancer journey such as curative intent treatment decision-making in prostate cancer (D' Alimonte et al 2011;Feldman-stewart et al 2001) or lymphedema in the breast cancer context (Dorri et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The expertise of health-care providers and the value of the peer-reviewed literature should not be discounted. However, the risks associated with not including patients and informal caregivers in developing questionnaires that are intended to assess their informational needs are important as discrepancies between what those receiving health care want to know and what those providing it feel is important to share are known to exist (Thiessen et al 2023). Data collected from these questionnaires may inform research conclusions and ultimately the evolution of clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semua responden memilih sumber informasi dari pelayanan kesehatan, dan sebanyak 44 responden (66.7%) memilih menggunakan sumber informasi dari pasien kanker serviks lainnya. Menurut penelitian yang dilakukan oleh Thiessen et al (2023) di Kanada, responden penelitian konsisten dan lebih mempercayai informasi yang diberikan oleh profesional layanan kesehatan dibandingkan sumber informasi lainnya. Sumber informasi adalah tempat seseorang mencari informasi untuk menambah pengetahuan dan dijadikan sebagai acuan untuk menentukan sikap yang benar, dan sumber informasi tidak terbatas pada pelayanan kesehatan saja tetapi juga dari televisi, internet, keuarga dan teman (Thiessen et al, 2023).…”
Section: Hasil Penelitian Dan Pembahasanunclassified
“…Menurut penelitian yang dilakukan oleh Thiessen et al (2023) di Kanada, responden penelitian konsisten dan lebih mempercayai informasi yang diberikan oleh profesional layanan kesehatan dibandingkan sumber informasi lainnya. Sumber informasi adalah tempat seseorang mencari informasi untuk menambah pengetahuan dan dijadikan sebagai acuan untuk menentukan sikap yang benar, dan sumber informasi tidak terbatas pada pelayanan kesehatan saja tetapi juga dari televisi, internet, keuarga dan teman (Thiessen et al, 2023). Seseorang memiliki tingkat kenyamanan yang berbeda-beda terhadap penyedia layanan kesehatan, dan lebih memilih mencari informasi kepada selain tenaga kesehatan.…”
Section: Hasil Penelitian Dan Pembahasanunclassified